DEVELOPMENT OF CATHELICIDIN IN LIPOSOME CARRIER USING THIN LAYER HYDRATION METHOD - CHAERUNISAA, ANIS YOHANA; DEWI, MAYANG KUSUMA; SRIWIDODO; JONI, I. MADE; DWIYANA, REIVA FARAH (International Journal of Applied Pharmaceutics, 2022)
Objective: The purpose of this study was to produce an optimum liposome formulation and to study the effect of formulation parameter such as phospholipid amount and hydration time on characteristics of liposome containing Cathelichidin. Methods: Liposomes were prepared using a thin layer hydration method. Characterization of liposomes included organoleptic, PSA (Particle Size Analyzer) and zeta potential, entrapment efficiency, morphology by TEM (Transmission Electron Microscopy), the chemical interaction by FTIR (Fourier Transform Infrared Spectroscopy), and the stability by using Freeze-Thaw method. Results: The result of the organoleptic test showed that the liposome were in the form of milky white dispersion, odorless, and without sedimentation. Optimum formula was obtained by making variations of soy oil: cholesterol 10: 0 (F1), 9: 1 (F2), 8: 2 (F3), 7: 3 (F4), and variations in sonication time (10 and 30 min). Based on the results, it was found that the optimum sonication time was 30 min. F2 and F3 were chosen as the most optimum formulas with particle sizes of 190.3±6.8 nm and 212.9±4.4 nm; polydispersity index of 0.192±0.023 and 0.137±0.022, and zeta potential as much as-38.8±0.6 mV and-34.8±2.0 mV. To the optimum formula, cathelicidin was loaded with hydration time varies of 100 and 120 min. Longer hydration time resulted in smaller particle size and higher entrapment efficiency either for F2 or F3. TEM characterization revealed a spherical shape of liposomes from the optimum formula. The results of FTIR characterization did not show any interaction between the phospholipids of liposomes with cathelicidin. The data from the stability test showed good stability for F2 and F3 with a hydration time of 120 min, indicated by a p-value>0.05, which indicated that there was no significant change in the zeta potential for three Freeze-Thaw cycles. Conclusion: Formula of liposom using a variation of soy oil: cholesterol 9:1 and 8:2 with hydration time of 120 min revealed the best result with good stability for three Freeze-Thaw cycles.